PEMANFAATAN LIMBAH AMPAS TAHU DALAM PEMBUATAN TEPUNG BERSERAT PANGAN TINGGI DAN RENDAH LEMAK SEBAGAI ALTERNATIF BAHAN PANGAN FUNGSIONAL - Ditta Kharisma Yolanda Putri; Hanggara Sudrajat; Ari Susanti; Susilowati; M. Wildan Ibnu Batuthoh (LP2M Universitas Jember, 2022)
Tofu is a source of vegetable protein that has high nutritional value for Indonesian Tofu, which is made from soybeans, produces waste from production, one of which is tofu dregs which cannot be stored for long and can pollute the environment. In general, the protein content in tofu dregs is still high, while until now its use is still relatively simple, namely only as animal feed. The content of tofu dregs which is still high in nutrition needs to be optimized for its use as an alternative functional food by processing it into tofu dregs flour, where in 100% tofu dregs flour contains 66.24% carbohydrates, 17.72% protein, 3.23% crude fiber, and 2.62% fat. However, the lack of knowledge about tofu dregs management, knowledge about nutrition and the benefits of tofu dregs, as well as the lack of innovation that can be applied from tofu dregs, causes most of the tofu manufacturing entrepreneurs to still consider the economic value of tofu dregs to be low. The solutions that have been provided include (1) Counseling on the nutritional content that is still present in tofu dregs (2) Socialization on methods that can be applied to process tofu dregs into flour and the benefits of tofu dregs flour. The result of this service activity is that partners get additional knowledge about the management of tofu dregs into high-fiber and low-fat food flour.